Laparoscopic sleeve gastrectomy without over-sewing of the staple line is effective and safe - Kasalicky, Mojmir; Dolezel, Radek; Vernerova, Eva; Haluzik, Martin (Wideochirurgia i Inne Techniki Mało Inwazyjne, 2014)
INTRODUCTION: Laparoscopic sleeve gastrectomy (LSG) is a bariatric procedure with very good long-term weight-reducing and metabolic effects. AIM: Here we report 6 years' experience with LSG performed in morbidly obese patients by one surgical team focusing on the impact of the degree of sleeve restriction and safety of the procedure without over-sewing the staple line. MATERIAL AND METHODS: From 2006 to 2012, 207 morbid obese patients with average age of 43.4 years and average body mass index 44.9 kg/m(2) underwent LSG without over-sewing the staple line. The complete 5- and 3-year follow-up is recorded in 59 and 117 patients with prospective data collection at 3, 6, 9, 12, 18, 24, 36, 42 and 60 months after LSG. Group 1 patients operated in 2006-2008 had smaller sleeve restriction. Group 2 patients operated in 2009-2012 had major sleeve restriction. All procedures were performed without over-sewing of the staple line. RESULTS: The average %EBMIL (excess body mass index loss) in group 1 patients with minor sleeve restriction reached 54.1% and average %EWL (excess weight loss) was 50.8% while in group 2 with major sleeve restriction the average %EBMIL reached 69.7% and average %EWL was 66.8%. Final weight reduction was significantly higher in group 2 patients compared to group 1 patients with smaller sleeve restriction. Out of 49 patients with preoperatively diagnosed T2DM (type 2 diabetes mellitus) was completely resolved in 70.8%. Pre-operatively diagnosed hypertension normalized in 64.2%, improved in 23.2%, and remained unchanged in 12.6% of patients. CONCLUSIONS: Carefully performed LSG without over-sewing the staple line is feasible and safe. A better weight-reducing effect was present in patients with major sleeve restriction.